Avian Retrovirus pp32 DNA-Binding Protein I. Recognition of Specific Sequences on Retrovirus DNA Terminal Repeats - Misra, Tapan K. (1982)
The avian retrovirus pp32 protein possesses a DNA-nicking activity which prefers supercoiled DNA as substrate. We have investigated the binding of pp32 to avian retrovirus long terminal repeat (LTR) DNA present in both supercoiled and linear forms. The cloned viral DNA was derived from unintegrated Schmidt-Ruppin A (SRA) DNA. A subclone of the viral DNA in pBR322 (termed pPvuII-DG) contains some src sequences, tandem copies of LTR sequences, and partial gag sequences in the order src-U(3) U(5):U(3) U(5)-gag. Binding of pp32 to supercoiled pPvuII-DG DNA followed by digestion of this complex with a multicut restriction enzyme (28 fragments total) permitted pp32 to preferentially retain on nitrocellulose filters two viral DNA fragments containing only LTR DNA sequences. In addition, pp32 also preferentially retained four plasmid DNA fragments containing either potential promoters or Tn3 “left-end” inverted repeat sequences. Mapping of the pp32 binding sites on viral LTR DNA was accomplished by using the DNase I footprinting technique. The pp32 protein, but not the avian retrovirus αβ DNA polymerase, is able to form a unique protein-DNA complex with selected regions of either SRA or Prague A LTR DNAs. Partial DNase I digestion of a 275-base pair SRA DNA fragment complexed with pp32 gives upon electrophoresis in denaturing gels a unique ladder pattern, with regions of diminished DNase I susceptibility from 6 to 10 nucleotides in length, in comparison with control digests in the absence of protein. The binding of pp32 to this fragment also yields enhanced DNase I-susceptible sites that are spaced between the areas protected from DNase I digestion. The protected region of this unique complex was a stretch of 170 ± 10 nucleotides that encompasses the presumed viral promoter site in U(3), which is adjacent to the src region, extends through U(5), and proceeds past the joint into U(3) for about 34 base pairs. No specific protection or DNase I enhancement by pp32 was observed in experiments with a 435-base pair SRA DNA fragment derived from a part of U(3) and the adjacent src region or a 55-base pair DNA fragment derived from another part of U(3). The DNA sequence of Prague A DNA at the fused LTRs differs from that of SRA DNA. The alteration in the sequence at the juncture of the LTRs prevented pp32 from forming a stable complex in this region of the LTR. Our results are relevant to two aspects of the interaction between pp32 and LTR DNA. First, the pp32 protein in the presence of selected viral DNA restriction fragments possibly forms a higher order oligomer analogous to Escherichia coli DNA gyrase-DNA complexes or eucaryotic nucleosome structures. Second, the specificity of the binding suggests a role for pp32 and the protected DNA sequences in the retrovirus life cycle. The preferred sequences to which pp32 binds include two adjacent 15-base pair inverted terminal repeats at the joint between U(5) and U(3) in SRA DNA. This region is involved in circularization of linear DNA and is perhaps the site that directs integration into cellular DNA.